The Role of Integrated Healthcare Center in Giving Service to Community of Cot Teugoh, Pidie Sub-District, Pidie Regency - Salahuddin; Ismail (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Integrated Healthcare Center is carried out by the community at the village level, once a month. The purpose of implementing Posyandu is to find out the Role of Integrated Service Post Officers (Posyandu) in optimizing services to the community in Teugoh Cot Village, Pidie District, Pidie Regency and to find out the barriers of Integrated Healthcare Center in optimizing services to the community in Teugoh Cot Village, Pidie District Pidie Regency by using a qualitative descriptive approach. The informants of this study were 1 midwife, 1 nurse, 1 Posyandu officer, 2 community members. The results of the study found that, 1) The role of Poyandu officers in Teugoh Cot Village was not optimal. Integrated Healthcare Center officers come to Geuceu Iniem Village only once a month, namely the fourth month. Integrated Healthcare Center officers arrive at 10:00 until 11:30 noon. In carrying out their duties, Posyandu officers work less optimally and in serving the community less effectively, 2) Obstacles faced by Integrated Healthcare Center officers, lack of funds in implementing Integrated Healthcare Center programs, both medical equipment and others. Given that Integrated Healthcare Center is a program from the Public health center, very little funding was obtained to process the Posyandu program for the better.